2020
DOI: 10.2147/opth.s219912
|View full text |Cite
|
Sign up to set email alerts
|

<p>Biometric Parameters and Corneal Astigmatism: Differences Between Male and Female Eyes</p>

Abstract: To evaluate the gender-related differences in demographic and ocular biometric trends in a defined population presenting for consultation within the Italian public health system and to collect data of several ocular parameters at different stages of life, highlighting the differences between females and males. Patients and Methods: In this retrospective study, keratometry, corneal astigmatism, and axial eye length of 729 patients (729 eyes; mean age: 58±21 years; range: 18-96 years) were evaluated using partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 35 publications
9
34
0
4
Order By: Relevance
“…However, there were statistically significant differences observed only in Lt CC. Multiple studies reported that females’ CC are steeper or higher than males’ [ 54 , 55 ]. The current study findings were in the same line as the earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were statistically significant differences observed only in Lt CC. Multiple studies reported that females’ CC are steeper or higher than males’ [ 54 , 55 ]. The current study findings were in the same line as the earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have been published on the correlation between AL and CT in emmetropic and myopic patients, most of them showing AL to be inversely related to subfoveal CT 20 , 31 35 .…”
Section: Discussionmentioning
confidence: 99%
“…These two studies prove the safety of this procedure, even if the efficacy was not so high. However, we would like to point out that in such a long-term study the ageing process could induce changes over the years, such as modifications in the lens index due to nuclear sclerosis, in the keratometric values, in the axial length (AL), and all these factors should be considered [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%